Safety and efficacy of repeated injections of botulinum toxin A in peripheral neuropathic pain (BOTNEP): a randomised, double-blind, placebo-controlled trial. Issue 6 (May 2016) - Attal, Nadine; de Andrade, Daniel C; Adam, Frédéric; Ranoux, Danièle; Teixeira, Manoel J; Galhardoni, Ricardo; Raicher, Irina; Üçeyler, Nurcan; Sommer, Claudia; Bouhassira, Didier
Summary: Background: Data from previous studies suggest that botulinum toxin A has analgesic effects against peripheral neuropathic pain, but the quality of the evidence is low. We aimed to assess the safety and efficacy of repeated administrations of botulinum toxin A in patients with neuropathic pain. Methods: We did a randomised, double-blind, placebo-controlled trial at two outpatient clinics in France (Clinical Pain Centre, Ambroise Paré Hospital, APHP, Boulogne-Billancourt, and Neurological Centre, Hôpital Dupuytren, Limoges) and one in Brazil (Neurological Department, Hospital das Clínicas da FMUSP, São Paulo). Patients aged 18–85 years with peripheral neuropathic pain were randomly assigned (1:1) by block randomisation, according to a centralised schedule, to receive two subcutaneous administrations of botulinum toxin A (up to 300 units) or placebo, 12 weeks apart. All patients and investigators were masked to treatment assignment. The primary outcome was the efficacy of botulinum toxin A versus placebo, measured as the change from baseline in self-reported mean weekly pain intensity over the course of 24 weeks from the first administration. The primary efficacy analysis was a mixed-model repeated-measures analysis in the intention-to-treat population. This trial is registered withClinicalTrials.gov, NCT01251211 . Findings: Between Oct 2, 2010, and Aug 2, 2013, 152 patients were enrolled, of whom 68 were randomly assigned (34 per group), and 66 (37 [56%] men) were included in the primary analysis (34 in the botulinum toxin A group and 32 in the placebo group). Botulinum toxin A reduced pain intensity over 24 weeks compared with placebo (adjusted effect estimate −0·77, 95% CI −0·95 to −0·59; p<0·0001). Pain on injection was the only adverse effect reported, and occurred in 19 (56%) participants in the botulinum toxin A group and 17 (53%) of those in the placebo group (p=1·0). Severe pain was experienced by ten (29%) participants in the botulinum toxin A group and 11 (34%) in the placebo group (p=0·8). Interpretation: Two administrations of botulinum toxin A, each of which comprised several injections, have a sustained analgesic effect against peripheral neuropathic pain. Several factors, such as the presence of allodynia and a limited thermal deficit, may be useful in predicting treatment response and should be investigated further. Funding: Institut National de la Santé et de la Recherche Médicale (INSERM) and Fondation CNP (France).